A Systematic Review on Aftercare for Youth Substance Users in Canada. Issue 4 (1st October 2016) - Hidalgo, Maricon; Sullivan, Ginger; Caine, Vera
ABSTRACT: In Canada, youth represent one of the groups most at risk for substance use and addiction. Many youth fail to receive adequate treatment and aftercare. The objective of this systematic review was to examine the existing evidence of youth aftercare programs in Canada. The authors conducted our systematic review according to the guidelines provided by PRISMA. Of the manuscripts reviewed in their search strategy, 4 studies met the criteria established. Despite several limitations of this systematic review, the need for more comprehensive and theoretically driven studies to examine the effectiveness and efficacy of aftercare treatment youth aftercare programs is evident.